Indahnya Betawi - Purbasari, Mita (Humaniora, 2010)
Frequently the uniqueness of Betawi with its superiority and shortage performance attracts many people. This article clarifies beauty in Betawi’s modest ethnic which concerns on history, artefact, culture, art, cloth and clothes’ motif, food, and ceremony relates to people’s life, by using cultural study method and structuralism theory. It is concluded that Betawi culture has been created through a long process, even though in fact they have been removed now, but the assimilation process with various ethnics in Indonesia makes Betawi ethnic is exist and recognized. Various arts together with cultural acculturation, language, and people arise multiple perceptions toward Betawi ethnic. The modesty factor causes Betawi ethnic can be accepted by all social levels in Indonesia. With cultural richness of Betawi, so that preservation on this culture is needed, considering on the Betawi’s characteristic which is less aware of their existence.